2019
DOI: 10.35940/ijrte.b1555.098319
|View full text |Cite
|
Sign up to set email alerts
|

Technology of Production of Technical Belts and the Study of Their Properties

Abstract: The article developed a method and technology for the production of seamless woven tapes. Defined technological parameters of the developed conveyor tapes. The laws of change in the mass and thickness of the conveyor tape made from the treated fabric, from the grey fabric and non-woven fabric depending on the time of operation are obtained. solved by the fact that the threading of the warp is carried out in the form of a continuous spiral, then the cords and weft yarns are woven into warp yarns the on the loom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…According to [5,14] we accept the stiffness of elastic filling system, C = 140 N/mm, therefore, from expression (1) the reduced stiffness to the middle radius of the driven disk Cpr = 10,1 N/mm. When the spring in the friction clutch is tightened λm = 12 mm, the friction forces are determined from expression (4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to [5,14] we accept the stiffness of elastic filling system, C = 140 N/mm, therefore, from expression (1) the reduced stiffness to the middle radius of the driven disk Cpr = 10,1 N/mm. When the spring in the friction clutch is tightened λm = 12 mm, the friction forces are determined from expression (4).…”
Section: Resultsmentioning
confidence: 99%
“…In [6,7,8,11,15] it is indicated that at low speeds of mutual sliding in the friction system there are jumps, which disappear when the speed increases, besides the amplitude and frequency of jumps depends on the sliding speed, mass of the ram and rigidity of the system. It is noted, in particular, that at a uniformly low velocity of the plane the ram will make the relaxation oscillations according to the sawtooth law (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation